ANALISIS KEAKTIFAN DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA DENGAN MOBILE LEARNING - Dhea Davina Dirganti; Baiq Rofina Arvy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This article discusses the analysis of student activity and learning outcomes in mathematics learning with mobile learning for class X MA Al-Chalil students. This research aims to see the impact of using mobile learning on quadratic function material. The research method used was descriptive qualitative involving 6 class X students as respondents. Student activity data is collected through observation sheets, and student learning outcomes are measured through cognitive tests and psychomotor tests. The research results show that the use of mobile learning in mathematics learning significantly increases student activity. There is a positive relationship between students' level of activity and their learning outcomes, indicating that students who are more active in learning mathematics with mobile learning tend to achieve better learning outcomes.